Enhancement of oxygen vacancies and solar photocatalytic activity of zinc oxide by incorporation of nonmetal - Patil, Ashokrao B.; Patil, Kashinath R.; Pardeshi, Satish K. (Journal of Solid State Chemistry, 2011)
B-doped ZnO and N-doped ZnO powders have been synthesized by mechanochemical method and characterized by TG-DTA, XRD, SEM-EDX, XPS, UV-visible and photoluminescence (PL) spectra. X-ray diffraction data suggests the hexagonal wurtzite structure for modified ZnO crystallites and the incorporation of nonmetal expands the lattice constants of ZnO. The room temperature PL spectra suggest more number of oxygen vacancies exist in nonmetal-doped ZnO than that of undoped zinc oxide. XPS analysis shows the substitution of some of the O atoms of ZnO by nonmetal atoms. Solar photocatalytic activity of B-doped ZnO, N-doped ZnO and undoped ZnO was compared by means of oxidative photocatalytic degradation (PCD) of Bisphenol A (BPA). B-doped ZnO showed better solar PCD efficiency as compare to N-doped ZnO and undoped ZnO. The PCD of BPA follows first order reaction kinetics. The detail mechanism of PCD of Bisphenol A was proposed with the identification of intermediates such as hydroquinone, benzene-1,2,4-triol and 4-(2-hydroxypropan-2-yl) phenol. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Bisphenol A; Enhanced oxygen vacancies; Nonmetal doping; Photocatalysis; Sunlight